PEMANFAATAN EKSTRAK BIJI MAHONI SEBAGAI PESTISIDA NABATI UNTUK MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera litura F) PADA PEMBIBITAN Acacia crassicarpa A. Cunn. ex Benth. - Rusandi, Rio; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Acacia crassicarpa is one kind of plant that was developed as industrial timber plantations. This plant has a rapid growth rate are very adaptable and tolerant of environmental conditions are extreme. Acacia crassicarpa nursery is a stretch of similar plants are very susceptible to the pests. One of the pests that often attack the young plants in the nursery is Spodoptera litura F. The efforts to control this pest is generally controlled by using chemical pesticides. The use of mahogany seed extract as a botanical pesticide for controlling Spodoptera litura F. of the Acacia crassicarpa nursery is an alternative that can be used as an environmentally friendly pesticide. This research aimed to know the potential of mahogany seed extract in controlling Spodoptera litura F. and determine the exact concentration of the level of Spodoptera litura F. mortality of the Acacia crassicarpa nursery. This research uses a Completely Randomized Design Method, which consists of 4 treatments and 4 replicates with concentration levels of botanical pesticide. T0 = concentration mahogany seed extract 0 g/l of water; T1 = 10 g/l of water; T2 = 20 g/l of water; T3 = 30 g/l of water. The results showed that the application of mahogany seed extract at the concentration of 30 g/l of water is the best concentration in controlling Spodoptera litura F. with results initial time of death fastest is 2.75 hours (2 hours 45 minutes), the fastest time of turning off 50% (LT50) is 18.00 hours and total mortality amounted to 72.50%. Keywords: Acacia crassicarpa, Spodoptera litura F., mahogany seed, botanical pesticide